How do you pee in space? - Krulik, Nancy E. (Krulik, Nancy E. George Brown, class clown, 2014)
In order to win an interview with an astronaut and a trip to space camp, George competes in a physical fitness contest, but in his determination to win, he misses how much this prize means to his friend, Alex.